Un no e un sì al "paragrafo ariano" nella chiesa: (i "Gutachten" di Marburg ed Erlangen) - Bonola, Gianfranco (Annali di storia dell'esegesi, 1999)
Two doctrinal documents basic to our understanding of the conflict that developed within the German Protestant Church immediately after the Nazi seizure of power are here translated unabridged into Italian for the first time. In 1933 the theological Faculties of Marburg and Erlangen, within a few days of each other, expressed opposite opinions on the question of whether the exclusion of non-Aryans from every position of public responsibility, decreed by the Third Reich, should be extended to the churches, so that pastors of Jewish origin would be deprived of their livings. The two opinions, backed up by arguments from Scripture, law and history, show in just a few pages the capacity (or incapacity) of theology to stand up to the impact of violent political and ideological pressure. An introductory note explains some of the details of the complex historical and cultural situation which are useful for a fuller understanding of the texts.